2018
DOI: 10.1111/dmcn.13923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mindfulness yoga programme MiYoga on attention, behaviour, and physical outcomes in cerebral palsy: a randomized controlled trial

Abstract: MiYoga, an embodied mindfulness-based movement programme, can enhance attention (more attentive and consistent performance) in children with cerebral palsy. MiYoga had no significant effect on physical functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 37 publications
3
77
1
1
Order By: Relevance
“…Trials suggested efficacy with acupuncture [227,228] and animal-assisted therapy [102] (yellow lights, weak positive). In contrast, conductive education [231,232], massage [238], reflexology [243], Vojta [244][245][246], and Yoga [248] were probably ineffective for improving motor skills (yellow lights, weak negative), and cranial sacral osteopathy [239][240][241] and hyperbaric oxygen [234] showed no between-group differences for motor skills in moderatequality trials and serious side effects occurred (red lights). Proponents of conductive education would claim that because the approach is holistic, that it is not reasonable to analyze indicators in isolation; nevertheless, these are the motor outcome results from published clinical trials.…”
Section: Motor Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trials suggested efficacy with acupuncture [227,228] and animal-assisted therapy [102] (yellow lights, weak positive). In contrast, conductive education [231,232], massage [238], reflexology [243], Vojta [244][245][246], and Yoga [248] were probably ineffective for improving motor skills (yellow lights, weak negative), and cranial sacral osteopathy [239][240][241] and hyperbaric oxygen [234] showed no between-group differences for motor skills in moderatequality trials and serious side effects occurred (red lights). Proponents of conductive education would claim that because the approach is holistic, that it is not reasonable to analyze indicators in isolation; nevertheless, these are the motor outcome results from published clinical trials.…”
Section: Motor Interventionsmentioning
confidence: 99%
“…The manual therapies, including massage (green light) [237] and cranial sacral osteopathy [241] and reflexology [243] (yellow lights, weak positive), appeared to help reduce constipation. Massage also appeared to help reduce pain [3•] (yellow light, weak positive), whereas Yoga did not [248] (yellow light, weak negative). However, Yoga did appear to improve attention, muscle flexibility, and balance (yellow light, weak positive) [248].…”
Section: Motor Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Diamond there are three core EFs (inhibition, working memory and cognitive flexibility) and from these, higher-order EFs are built (reasoning, problem solving and planning & monitoring) [23]. There have been some home-based randomized controlled trials (RCT) in children with CP focused on a single domain of EF such as working memory using the Cogmed System [24] and attention using the MiYoga Programme [25]. Previous studies in other populations indicate that training more than one EF domain allows the transference of improvements to other cognitive functions or clinical symptoms [26,27].…”
Section: Home-based Multi-modal Computerized Training In Cpmentioning
confidence: 99%
“…Mak et al's investigation of the benefits of an increasingly popular OPA program for children called MiYoga reported improvements in attention for children with cerebral palsy (CP). Although CP is not considered a neurodevelopmental condition, it is associated with many neurodevelopmental comorbidities, such as attention‐deficit–hyperactivity disorders and intellectual disability.…”
mentioning
confidence: 99%